Functional Differentiation of Floral Color and Scent in Gall Midge Pollination: A Study of a Schisandraceae Plant - Shi-Rui Gan; Wei Du; Xiao-Fan Wang (Plants, 2022)
Gall midges are among the most host-specific insects. Their interactions with plants likely date back to the Cretaceous period. Plants from at least seven families are involved in gall midge pollination; however, little is known about the pollination signals of gall midges. In this study, we used a Resseliella–Schisandra model to investigate the roles of floral scent and color in attracting gall midges. Field observations, behavioral bioassays via Y-tubes, and “flight box” experiments were performed. The results demonstrated that gall midges may be attracted by both floral scent and color and that two flower signals are more effective in promoting insect flower-landing than either alone. In the field, gall midges visited male flowers effectively at night but almost always visited female flowers during the day. Thus, during the Resseliella–Schisandra interactions, female flowers predominantly employed visual cues over scent to attract midges during the day; in contrast, olfactory cues were more functional for male flowers to export pollen in the dark. In this study, we first identified the roles of floral color and the functional differentiation of visual and olfactory cues during gall midge pollination.